Cyberbullying e ambiência escolar: os adolescentes e seus professores convivendo na cultura digital - Flora, Francieli Lorenzi Fracari Della (2014)
This master thesis is linked to the Line of Research: Education, Knowledge and Professional Development of the Program of Post-graduationin Education (PPGE at the Universidade Federal de Santa Maria). It is focused on the digital violence and interpersonal relationships between adolescents in school environment and as the main aim to investigate to what extent the possible actions of cyberbullying may impact a school ambience, considering how they think and act young people and their teachers. The specific research objectives are to identify predominant characteristics in individuals who suffer and/or practice violence of cyberbullying; to understand feelings present in individuals suffering and/or practice cyberbullying and analyze behavior of confront and survival strategies developed by cyberbullying teens and teachers. Therefore, we address the issue of cyberbullying under a different perspective, involving the virtual context and the school ambience, considering as individuals, students and teachers of a public school in the municipality of Santa Maria/RS. This is a qualitative research of a case study, using the mixed methods, which use quantitative and qualitative data in the same research. The research instruments were questionnaires and narrative interview. Interpretation of the data was performed by Textual Discourse Analysis (TDA), from the perspective of Moraes; Galiazzi (2007). The results were possible to study the characteristics of the individuals, as well targets and authors, as well as the consequences and feelings expressed by the study individuals. Furthermore, it allowed the understanding of the occurrence of cyberbullying fact reflected in interpersonal relationships and influence on school ambience. Finally, we hope that this study adds to the scientific literature about school violence, in order to broaden the thematic, addressing new aspects about cyberbullying, aiding in minimization process of the same, and contribute to the reflection of the contemporary school.